Enrichment/Population of Customized CPR (Computer-based Patient Record) Ontology from Free-text Reports for CSI (Computer Semantic Interoperability - Mendes, David (2013)
CSI (Computer Semantic Interoperability) is a very important issue in healthcare. Ways for heterogeneous computer systems to “understand” important facts from the clinical process for clinical decision support are now beginning to be addressed. We present here comprehensive contributions to achieve CSI. EHR (Electronic Health Record) systems provide a way to extract reports of the clinicians activity. In order to formalize an automated acquisition from semi-structured, free-form, natural language texts in Portuguese into a Clinical Practice Ontology an important step is to develop the ability of decoding all the nicknames, acronyms and short-hand forms that each clinician tend to write down in their reports. We present the steps to develop clinical vocabularies extracting directly from clinical reports in Portuguese available in the SAM (Sistema de Apoio ao Médico) system. The presented techniques are easily further developed for any other natural language or knowledge representation framework with due adaptations.